Tantangan Pendidikan Keluarga Islami di Era Pandemi Covid-19 (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2022)
The Covid-19 pandemic in Indonesia brought major changes in the world of education. Government provisions regarding restrictions on physical interactions between people require everyone to carry out activities in private spaces. Everything that was originally done in the public space was 'forced' to change. A revolution in learning has occurred at all levels of education which requires students and teachers to no longer interact physically in the classroom but in virtual classrooms. The Transition have never been carried out on a massive scale has shocked both teachers and students. The purpose of this study was to find out the challenges faced by families in implementing education during the Covid-19 pandemic. This study uses a qualitative approach by analyzing Islamic education books and the arguments related to education in the family. The researcher took a contextual approach in assessing the adaptation of existing theory to the actual conditions at the time the research was conducted during the Covid-19 pandemic. The data were then analyzed including data collection, data reduction, data presentation and drawing conclusions. The results of the study concluded that education during the pandemic underwent drastic changes with the use of a distance learning system, which was never done by most Indonesians before. This requires adaptation for teachers, students and also parents. This major change also reminds us that the role of the family returns to its essence as the first and foremost institution in educating humans, fathers and mothers are educators while their children act as students. The challenge of Islamic family education during the Covid-19 pandemic is education in the family. In essence, education begins in the family as the smallest environment for parents, children first receive guidance and coaching, before they enter the school environment and the wider community.